Teachers and Urban-Rural Gaps in Educational Outcomes. (11th April 2018) - Zhang, Jian; Jin, Songqing; Torero, Maximo; Li, Tao
Abstract: We examine the role of teachers in explaining the urban-rural gap in educational outcomes. Using a large panel data set of students and teachers collected from China and explicitly controlling for the endogeneity of prior student academic achievement, we find that the urban-rural difference in teacher effects contributes in large part to the observed urban-rural gap in student academic achievement. In other words, if rural teachers were of the same quality as urban teachers, the urban-rural gap in student academic achievement would be reduced substantially.